Pengaruh Budaya Organisasi dan Lingkungan Kerja Terhadap Layanan Perbankan PT. Bank Mega Tbk - Loeky Alamsah; Ana Ramadhayanti (Indo Publishing, 2025)
Banking service is one of the key factors supporting the achievement of a company’s objectives. To encourage excellent service, organizational culture and work environment are aspects that management needs to pay attention to. This study aims to analyze the partial effect of organizational culture on banking services, analyze the partial effect of work environment on banking services, and examine the simultaneous impact of both variables on banking services. The research results indicate that both Organizational Culture (X1) and Work Environment (X2) have positive and significant influences on Banking Services (Y). Simultaneous testing shows that both variables collectively contribute significantly to service improvement, indicated by an F-value of 75.564 with a significance level of 0.001. This finding implies that implementing effective Organizational Culture (X1) and conducive Work Environment (X2) can enhance Banking Services (Y) within PT. Bank Mega, Tbk.